2015
DOI: 10.1186/1471-2490-15-6
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol for premature ejaculation: a systematic review and meta-analysis

Abstract: BackgroundTramadol is a centrally acting analgesic prescribed off-label for the treatment of premature ejaculation (PE). However, tramadol may cause addiction and difficulty in breathing and the beneficial effect of tramadol in PE is yet not supported by a high level of evidence. The purpose of this study was to systematically review the evidence from randomised controlled trials (RCT) for tramadol in the management of PE.MethodsWe searched bibliographic databases including MEDLINE to August 2014 for RCTs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Tramadol also caused a significant decline in Leydig cells activities (Nna et al , ) with a possible reduction in testosterone biosynthesis. Although tramadol has been reported to improve premature ejaculation but adversely affect male reproduction (Hashem et al , ; Martyn‐St James et al , ; Nna et al , ), it is structurally different from other members of the opioid family (McMillan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tramadol also caused a significant decline in Leydig cells activities (Nna et al , ) with a possible reduction in testosterone biosynthesis. Although tramadol has been reported to improve premature ejaculation but adversely affect male reproduction (Hashem et al , ; Martyn‐St James et al , ; Nna et al , ), it is structurally different from other members of the opioid family (McMillan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Nigeria, the rate of tramadol abuse has been on the increase among Nigerian youths in recent time [14]. The main factor responsible for this could be link to off-label use of tramadol as ondemand treatment for premature ejaculation (PE) [15,16]. However, wide-spread use of tramadol is associated with toxicity and a recent study showed that tramadol cause brain, heart and lung toxicity [17].…”
Section: Introductionmentioning
confidence: 99%
“…Patients also reported significantly greater satisfaction with tramadol ( 84 ). Another meta-analysis of eight trials had similar results but was limited by heterogeneity amongst the individual studies ( 87 ). Doses from 25–100 mg have been tested and determined to be safe and effective ( 85 ).…”
Section: Disorders Of Ejaculationmentioning
confidence: 98%